2010
DOI: 10.1111/j.1751-1097.2010.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Antimicrobial Photodynamic Therapy: A Novel Technique for Efficient Eradication of Pathogenic Bacteria

Abstract: The increasing resistance of bacteria to antibiotics is a serious problem, caused in part by excessive and improper use of these drugs. One alternative to traditional antibiotic therapy is photodynamic antimicrobial chemotherapy (PACT) which is based on the use of a photosensitizer (PS), activated by illumination with visible light. The poor penetration of visible light through the skin limits the application of PACT to the treatment of skin infections or the use of invasive procedures. To overcome this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…These results were explained by differences in photosensitizer chemistry which may influence their association with liposomal components, lipid fluidity and localization in liposome vesicles (Ferro et al, 2006;2007). We have previously shown that Methylene Blue encapsulated in liposomes composed of DPPC or EPC effectively deactivated several Gram-positive and Gram-negative bacteria, including S. lutea, E. coli, S. flexneri, S. aureus and MRSA, and that liposomal Rose Bengal also eradicated P. aeruginosa Nakonechny et al, 2010;.…”
Section: Bactericidal Properties Of Photosensitizers Encapsulated In mentioning
confidence: 99%
“…These results were explained by differences in photosensitizer chemistry which may influence their association with liposomal components, lipid fluidity and localization in liposome vesicles (Ferro et al, 2006;2007). We have previously shown that Methylene Blue encapsulated in liposomes composed of DPPC or EPC effectively deactivated several Gram-positive and Gram-negative bacteria, including S. lutea, E. coli, S. flexneri, S. aureus and MRSA, and that liposomal Rose Bengal also eradicated P. aeruginosa Nakonechny et al, 2010;.…”
Section: Bactericidal Properties Of Photosensitizers Encapsulated In mentioning
confidence: 99%
“…In fact, it has been shown to significantly eradicate Staphylococcus sp [14, 23, 24], Pseudomonas sp 6 , or Candida sp [25]. Many studies have also shown the efficacy of PDT using in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…This method is more widely used for oral pathologies [10], but its application in the otologic field remains to be defined. Many studies have demonstrated the efficacy of photodynamic antimicrobial chemotherapy using methylene blue as a photosensitizer [11-13] including effectiveness against most common pathogens found in chronic otitis, such as Staphylococcus aureus or Pseudomonas aeruginosa [9, 14-16]. …”
Section: Introductionmentioning
confidence: 99%
“…When activated by light, it transfers energy to molecular oxygen, resulting in production of reactive oxygen species including singlet oxygen, superoxide ions, hydroxyls, and other free radicals that lead to direct damage of cellular components. 18,19 The advantages of PACT were discussed in a recent review 20 : it is equally effective against antibioticresistant and antibiotic-susceptible bacteria. The development of resistance to PACT appears to be unlikely, since, in microbial cells, singlet oxygen and free radicals interact with several cell structures and different metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%